SISTEM INFORMASI ASET (SIMaset) BARANG DAN DOKUMEN BERBASIS WEB - Miftahul Jannah; Suhartono Suhartono; Udin Sidik Sidin (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2021)
Web-based asset management needs to be developed to facilitate data collection of goods and documents in higher education because it is related to data security. It is necessary to develop an online information system that is accurate and easy. This research is in the form of software development research which aims to develop a web-based SIMAset application and test the quality of the application based on the ISO25010 quality standard which consists of aspects of Functionality, Reliability, Portability and Usability. The method used is R & D. The development model used in this research is Prototype. Based on the results of the research, a web-based application is produced that can be used in online college inventory management. The results of the validation test from the expert team showed that the SIMaset developed was very suitable to be used as an information system for managing goods and inventory documents. For further research, this system will develop certain menus that are tailored to the needs of asset and document archiving.